Morphopragmatic Features of Japanese Diminutives: A Literature Review - Adnyani, Kadek Eva Krishna; Pramesti, Putu Dewi Merlyna Yuda; Hermawan, Gede Satya (Chi e Journal of Japanese Learning and Teaching, 2025)
Diminutives play a significant role in communication directed toward infants and children, serving both linguistic and social functions. However, studies that specifically and comprehensively examine diminutives in the Japanese language remain limited. This literature review aims to describe the morphological forms and semantic meanings of Japanese diminutives based on previous research. The study adopts a qualitative descriptive approach using a narrative literature review method. In Japanese, diminutives appear in various grammatical forms, including honorific name suffixes (e.g., -chan), performative honorifics (e.g., -dechu), nouns (e.g., uchagi), adjectives (e.g., kuchai), adverbs (e.g., chukochi), verbs (e.g., achobu), and adpositional forms (e.g., chochite). The meanings of these diminutives are context-dependent and can be interpreted within the conceptual framework proposed by Schneider, encompassing notions such as smallness, affection, and sweetness. By synthesizing existing studies, this review contributes to a deeper understanding of the morphopragmatic and sociolinguistic functions of diminutives in Japanese. It also highlights the need for further research to explore their broader communicative and cultural significance in everyday interaction.